RELATIONSHIP BETWEEN CHLOROPHYLL AND PHYTOPLANKT ON IN REWALSAR LAKE, HIMACHAL PRADESH - CHAUHAN, RAMESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Monthly variations in Chlorophyll concentration and phytoplankton of Rewalsar lake have been estimated and enumerated respectively. The column averaged chlorophylls showed trimodal peaks corresponding to phytoplankton populations. Relationships developed among different Chlorop yils and phytoplankton groups revealed significant and positive relationship of chlorophyll-a with Myxophytes at d highly significant and positive relationship of chlorophyll-c with Bacillariophytes and total phytoplankton. Total chlorophyll content (chlorophyll-a+b+c) also showed highly significant and positive relationship with total phytoplankton population.